2014
DOI: 10.1136/tobaccocontrol-2014-051744
|View full text |Cite
|
Sign up to set email alerts
|

High levels of tobacco-specificN-nitrosamines and nicotine in Chaini Khaini, a product marketed as snus

Abstract: Introduction Recently, a tobacco product, Chaini Khaini, identified as snus appeared in India. The product marketing emphasizes its discreet nature and explicitly claims safety by referring to the existing evidence on Swedish snus. We here analyzed tobacco-specific nitrosamines and nicotine in 12 samples of Chaini Khaini purchased in 2013 at open markets in India. Methods Samples were purchased twice: in March 2013 from Mumbai and in November 2013 from Mumbai and Ahmedabad. Chemical constituents were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…In India, a smokeless product known as Chaini Khaini is marketed as a snus equivalent. A study of Chaini Khaini was performed to determine its actual carcinogen content and whether it is similar to snus . Stepanov et al analyzed TSNA, nicotine, and unprotonated nicotine in samples of this product purchased in India.…”
Section: Using Tobacco Carcinogen Research To Inform Public Policymentioning
confidence: 99%
See 1 more Smart Citation
“…In India, a smokeless product known as Chaini Khaini is marketed as a snus equivalent. A study of Chaini Khaini was performed to determine its actual carcinogen content and whether it is similar to snus . Stepanov et al analyzed TSNA, nicotine, and unprotonated nicotine in samples of this product purchased in India.…”
Section: Using Tobacco Carcinogen Research To Inform Public Policymentioning
confidence: 99%
“…A study of Chaini Khaini was performed to determine its actual carcinogen content and whether it is similar to snus. 25 Stepanov et al analyzed TSNA, nicotine, and unprotonated nicotine in samples of this product purchased in India. The authors demonstrated that Chaini Khaini actually had high levels of carcinogenic TSNA, contrary to its marketing.…”
Section: Using Tobacco Carcinogen Research To Inform Public Policymentioning
confidence: 99%
“…Second, our conclusions are also restricted to the specific varieties of snus and nicotine gum used in this study (Camel® Winterchill™ snus and Nicorette® FreshMint™). The complex, evolving marketplace for snus and medicinal nicotine features heterogeneity in nicotine content, flavor, and quality (Digard et al 2013; Stepanov et al 2012a,b, 2015), which poses research challenges and may limit general conclusions. However, mint flavors of smokeless tobacco and medicinal nicotine appear the most popular among clinical trial participants (Meier et al 2016); thus, the flavors used in the present study were those shown in prior work to be widely preferred.…”
Section: Limitationsmentioning
confidence: 99%
“…Such an approach may be valuable, as recent data indicate that use of snus in the USA is strongly associated with a desire to reduce cigarette consumption (Biener et al 2014); moreover, snus produces therapeutic outcomes similar to medicinal nicotine gum in attempts at smoking cessation (Hatsukami et al 2016; Kotlyar et al 2011). However, despite the perception that snus is safer than cigarettes, snus poses greater health risks than medicinal nicotine (Hatsukami et al 2016; Kotlyar et al 2011) and its carcinogen and nicotine content appear unstable in an evolving marketplace (Stepanov et al 2012a,b, 2015). …”
mentioning
confidence: 99%
“…There is considerable diversity of SLT products, but those commonly used in the SEAR, and notably in India, include highly toxic forms, with very high levels of harmful constituents such as nitrosamines and heavy metals [2, 7, 8]. SLT products in SEAR have been shown to cause a broad range of diseases and adverse health effects such as various types of cancers, cardiovascular disease, and adverse pregnancy outcomes [1, 2, 5, 6, 911].…”
Section: Introductionmentioning
confidence: 99%